International Art Fair "Art Moscow". - Art Moscow 1997 (Moscow : Art Moscow, 1997)
Steinbach, Haim ; Infante, Francisco ; Makarevich, Igor ; Fishkin, Vadim ; Pertchikhina, Marina ; Abramishvill, Gia ; Pishchukevich, Igor ; Brandstätter, Karl ; Dussau, Georges ; Kulik, Oleg ; Voronova, Lucia ; Baumgartel, Thomas ; Varfolomelevich, Pavel ; Klutsis, Gustav Gustavovich ; Ibragimov, Kanat ; Koshkin, Alexandr ; Semionov, Alexei ; Avvakumov, Yuri ; Brainin, Vladimir ; Elagina, Iya GigoshvillElena ; Martinchik, Svetlana ; Efimov, Vladislav ; Chernishev, Aristarkh
International Art Fair "Art Moscow", March 3-8 1997
boek